Optimization of Hardness Improvement of Bucket Wheel Excavator (BWE) Trackplate Bushing Material Based on the Taguchi Method - Hendryanto, Refdinal Latif; Hendryanto, Refaldy Yusuf; Arifin, Amir (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
trackplate’s bushing material made of AISI 4340 steel through heat treatment designed using the Taguchi method. The heat treatment process includes several key parameters, namely austenitizing temperature, austenitizing time, quenching media, and tempering time, which are systematically evaluated to maximize the increase in material hardness. The experimental design employs the Taguchi method with an L9 orthogonal array to determine the optimal combination of parameters from four factors and three levels of variables, including austenitizing temperatures of 870°C, 900°C, and 925°C; austenitizing times of 25, 30, and 35 minutes; quenching media of water, salt water, and oil; and tempering times of 1.5, 2, and 2.5 hours. Hardness testing conducted using the Rockwell HRC scale shows that the optimal combination is achieved at an austenitizing temperature of 925°C, an austenitizing time of 35 minutes, salt water as the quenching media, and a tempering time of 2.5 hours. This combination successfully increases the material hardness to 56.9 HRC, representing an increase of 67.84% from the initial hardness of 33.9 HRC. S/N ratio analysis reveals that quenching media and austenitizing temperature significantly impact the increase in hardness. At the same time, tempering time plays a role in stabilizing the martensitic structure without reducing the achieved hardness. The results of this study demonstrate that the Taguchi method effectively determines the optimal heat treatment parameters for bushing materials, thus producing material hardness that meets the required technical specifications.Keywords: AISI 4340 Steel, bushing, hardness improvement, heat treatment, Taguchi method, S/N ratio analysis.